Das Verbrechen als Rechtsverletzung Subjektive Rechte im Strafrecht - Hirsch, Philipp-Alexander (Strafrechtliche Abhandlungen. Neue Folge (SRA), 2021)
»The Wrongfulness of Crimes. On Rights and Rights Violations in Criminal Law«: The thesis challenges a common view in criminal law theory, which understands criminal wrongdoing as offences against the state. Instead, the author proposes a paradigm shift arguing that crimes are conceivable as intersubjective right violations and simultaneously as violations of the legal community. Thus, the book provides the foundation for a better understanding of the role of victims in criminal law and an innovative critical standard for evaluating criminal law and criminal procedure.